Reconstruction of General Relativistic Phenomena and Localization Model of Quantum Entanglement Based on UCST Unified Realism - Cui, Weicheng (European Journal of Applied Sciences, 2026)
Within modern physics, classical mechanics, general relativity (GR) and quantum mechanics adopt mutually exclusive ontological assumptions, creating persistent irreconcilable contradictions. GR describes gravitation via spacetime curvature yet suffers from spacetime singularities, unobserved dark matter/dark energy hypotheses, and fundamental incompatibility with quantum theory. Quantum entanglement is conventionally interpreted as nonlocal correlation, violating classical locality and triggering decades of foundational physics debate. Based on Unified Complex System Theory (UCST, Unified Realism), this paper establishes four core ontological postulates: active-passive force dichotomy, universal gaseous air medium for force transmission, absolute flat space paired with relative descriptive time, and generalized living entities. This framework abandons the spacetime curvature hypothesis entirely and constructs a unified physical interpretation system built on coupling between gaseous air medium perturbations and interactive forces. Constrained by locality, slow attenuation and experimental self-consistency, three hierarchical entanglement intensity decay functions are derived to achieve fully localized quantum entanglement modeling, integrating quantum correlations into UCST’s medium-mediated force transmission architecture. UCST reproduces all validated classical mechanical results and quantitatively recovers core relativistic astronomical observables—Mercury/Venus perihelion precession, gravitational light deflection, gravitational redshift, black hole physics, gravitational lensing and gravitational waves—without invoking geometric spacetime constructs. The three proposed entanglement decay functions satisfy strict locality constraints while matching long-range quantum communication experimental measurements, resolving quantum mechanics’ nonlocality paradox. This work forms a quantitatively complete, logically closed unified theoretical paradigm spanning macroscopic astrophysics and microscopic quantum physics, offering a novel research pathway for the grand unification of fundamental physics.